Reduction of excavation face collapse risk in tunnelling - Ariani, Filippo; Baldasseroni, Alberto; Muller, Alessandro; Biffino, Marco; Matteucci, Alessandro (La Medicina del Lavoro, 2017)
Two large road tunnels, recently developed near Florence, showed instabilities of the excavation face which subsequently caused sixteen collapses. Due to the risk for workers’ safety, the public authority for occupational health and safety (ASL) has monitored the failure rate and other background variables in order to assess the possible correlations between risk reductions, its own actions, and those of the various safety actors involved. Objectives: To evaluate if the interventions carried out by the design team were able to reduce the risks of collapse and which of the ASL actions and/or which other factors were more effective in changing the attitudes of the parties involved, leading to a more expensive but safer project variant. Results: After adoption of the second of two project variants, no more collapses were observed. No correlation was found between trend of ASL inspections and observed variation of collapse rate. Conversely, the adoption of strongly coercive measures and investigation reporting by local media coincided with periods of risk reduction, even if the low number of events does not allow for statistical evaluation. Conclusions: These findings appear to be coherent with the ratio of the cost of penalties related to health and safety infringements (thousands of euros) to the overall cost of the safer project variant (a hundred times greater). The safer variant required 7% more labour but avoided forced interruptions caused by the collapses, allowing a 13% faster excavation rate.